Making the move to eLearning [ putting your course online - Lehmann, Kay Johnson , 1957-; Chamberlin, Lisa , 1966- (Rowman & Littlefield Education, 2009)
Making the Move to eLearning proposes a radical truth--that online education, when taught using the methodology perfected by successful veterans of distance learning, surpasses traditional face-to-face teaching and learning. The key is for online educators to learn just what those successful methods are and how to emulate them in their own virtual courses. Making the Move to eLearning is the textbook for new and